KONTRAK PSIKOLOGIS DAN ETOS KERJA PADA KARYAWAN KONTRAK - Anggarini Briliani; Retno Dwiyanti (Psycho Idea, 2018)
This research aims to know the impact of psychological contract to work ethic of oursourcing employees at University X. The hypothesis proposed in this research is there is an impact of psychological factor to work ethic of outsourcing employees at University X. This research employed quantitative research using linear regression technique to know the impact of psychological contract to work ethich of outsourcing employees at University X. There were 63 employees taken for the sample, consisted of driver, security guard, administration staff, laboratory assistant, technician, executive assistant, programmer, matron, instructure, and librarian. The data collection used were scale of work ethic and scale of psychological contract. The reliability of work ethic is 0.893 and reliability of psychological contract is 0.919. The results reveal that F obtained is 35.111 with p=0.000 (p<0.01), so the hypothesis is accepted. It means there is a significant impact between psychological factor and work ethic to outsourcing employees at University X and psychological contract contributes 42.9% to work ethic of outsourcing employees (R = square = 0,429). Keywords: Psychological Contract, Work Ethic, Outsourcing Employees